KEMAMPUAN SISWA MENGGUNAKAN KONJUNGSI INTRAKALIMAT DAN EKSTRAKALIMAT DALAM KARANGAN NARASI - Rasmijah Rasmijah (EDU-KATA, 2018)
The purpose of the study were to describe (1) the types of conjunction intra-sentence, (2) the types of conjunction extra-sentence, (3) the students’ ability in describing the function of conjuction in intra-sentence, and (4) the students’ ability in describing the function of conjunction in extra-sentence of naration text at the eighth graders H of the first state Madrasah Tsanawiyah Bojonegoro. The study was descriptive qualitative research. The data analysis technique used was interactive model from Milles and Huberman. The interactive model consisted of data reduction, data representation, and conclusion. The result showed that in the narration text of the students there are intra-sentence conjuntion and extra-sentence conjunction. The conjunction of intra-sentence included agar, biarpun karena, walaupun sambil, kalaupun, seolah-olah, gara-gara, tapi, selain meskipun sehingga, lalu, selain, kendatipun, jika, ketika, asalkan, seandainya. The conjunction of extra-sentence included oleh karena itu,bahkan, meskipun demikian, sekalipun begitu. The function of conjunction were hope, contrary, cause, requirements, purpose, comparison, time, addition, sequence, effect, supposition.